Radicular cyst associated with a primary molar: a rare case report and follow-up - Almeida de Deus Moura, Lucia de Fátima; de Deus Moura de Lima, Marina; Silva de Moura, Joyce Samandra; Gonçalves Nogueira, Natália; Vaz Soares Castro, Marcus Victor; de Deus Moura, Rafael (Jornal de Ciências da Saúde do Hospital Universitário da Universidade Federal do Piauí, 2022)
Introduction: The development of radicular cysts in primary dentition is an unusual occurrence. A relation with pulp treatments has been reported and represent an issue to be considered on treatments follow up. Case description: A seven-year-old female child had a necrosed mandibular right second primary molar pulpectomized with zinc oxide and eugenol paste. At the nine-month radiographic evaluation, there was an image compatible with a radicular cyst. Dental extraction with enucleation of the cyst was made. Histopathological evaluation confirmed the diagnosis of radicular cyst. At the 18-month, after surgical procedure, the premolar showed crown eruption and radiographic normality. Conclusion: Follow up schedule is important to interfere soonely in case of pathological infectious reaction after pulp treatments in primary teeth.